Facilitating SARS-CoV-2 RNA-Dependent RNA Polymerase (RdRp) Drug Discovery by the Aid of HCV NS5B Palm Domain Binders: In Silico Approaches and Benchmarking - khaled, laila (AUC Knowledge Fountain, 2021)
Corona Virus 2019 Disease (COVID-19) is a rapidly emerging pandemic caused by a newly discovered beta coronavirus, called Sever Acute Respiratory Syndrome Coronavirus 2 (SARS COV-2). SARS COV-2 is an enveloped, single stranded RNA virus that depends on RNA dependent RNA polymerase (RdRp) to replicate. Therefore, SARS COV-2 RdRp is considered as a promising target to cease virus replication. SARS COV-2 polymerase shows high structural similarity to Hepatitis C Virus-1b genotype (HCV-1b) polymerase. In our present study, we are relying on in-silico analysis to propose possible SARS COV-2 RdRp palm subdomain inhibitors to be used as a remedy for COVID-19. Additionally, providing an example of how to make use of a high quality custom-made DEKOIS 2.0 benchmark set as a procedure to elevate the virtual screening success rate against a vital target of the rapidly emerging pandemic. Arising from the high similarity between SARS COV-2 RdRp and HCV-1b polymerase, we used the reported small-molecule palm binders to HCV-1b polymerase to generate a high-quality DEKOIS 2.0 benchmark set and conducted a benchmarking against HCV-1b polymerase. The three highly cited and publicly available docking tools AutoDock Vina, FRED and PLANTS were benchmarked. Based on the benchmarking analysis, we used the highest performing docking tool to virtually screen FDA-approved drugs (from the DrugBank database) and the BindingDB database against the palm site of SARS COV-2 polymerase. From the benchmarking results, PLANTS showed the best performance with pROC-AUC value equals 0.97. Moreover, AutoDock Vina exhibited better-than-random performance with pROC-AUC value of 0.66 (above 0.43). Based on the virtual screening outcome, Quinupristin, which is an anti-biotic used in several bacterial infections, showed the best docking score among the screened compounds. In conclusion, Quinupristin as well as the top docking scored compounds are recommended to be biologically investigated as COVID-19 medications.